Histrionic personality disorder to some groups of women in Erbil city - Akar Abdul Majeed Ghagour; Moaid Ismail Jarjis (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The Histrionic Personality arises from the interaction of genetic and environmental factors, the relationship of the individual to the parents (particularly through improper socialization) and this personality is the result of backwardness or failure in the process of emotional maturity, and we cannot consider this character a disease in itself, but it is a Personality Disorder, thus, this research attempts to investigate the extent of the in Histrionic Personality Disorder in a sample of (300) women from different groups in the city of Erbil. The researcher aims to illustrate the following: 1- Indicators of the prevalence of Histrionic Personality Disorder in the total sample. 2 - Significance of statistical differences in Histrionic Personality Disorder according to age, marital status and women groups. The current research has determined the following: 1- The human scope: The current research is determined by groups of women (female teachers in high schools, female employees in Government Departments, students at Salahaddin-Erbil University and Lebanese French University, including patients in women's hospitals and clinics. 2 - Time: 2018-2019 3 – Place: The city of Erbil. In the current research, the researcher relied on the following procedures to obtain the one questionnaire: 1- The researcher relied on the questionnaire of (Qadoomi, 2000) and the questionnaire of (Omar, 2009) and (DSM-5) for the questionnaire of Histological Personality Disorder. 2- Presentation of items of (Histrionic Personality Disorder) to a group of experts in education and psychology to extract the apparent sincerity of the on questionnaire, as well as extract the echo of construction. 3- A sample of (300) women was randomly selected. 4 - Analysis of the items of the questionnaire in the method of the upper and lower groups. 5- Extracting the stability of the questionnaire by re-test method, which reached in the questionnaire of the Personality Disorder (** 0.62) and in the mid-split method of the questionnaire of Personality Disorder (0.799). After the implementation of the questionnaire of Histrionic Personality Disorder on the individuals of the sample and the analysis of their data statistically using (SPSS) was reached the following results: The mean of the scores of the sample individuals on the questionnaire of Histrionic Personality Disorder (58.48) degree and standard deviation of (5.76) degrees and was statistically significant from the level (0.00) when compared to the hypothesis mean of the questionnaire and its value (63) degree. 2- There are statistically significant differences in the Histrionic Personality Disorder of the sample among the individuals according to the variable (age and groups of women) and the absence of statistically significant differences according to the variable marital status.